A Positive View on Conflicts: Conflict Resolution at School, an Opportunity to Enhance Socio-Emotional Learning - Silva , Lorena (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2019)
Conflicts are part of our daily lives; moreover, they are essential in our personal and social development. This paper aims to reflect on the need to overcome the negative view on school conflicts, thus proposing a positive view considering them as a true chance to promote socio-emotional learning. Diverse aspects related to conflict and emotional education are analysed, like the true role of teachers, the emotional impact of conflicts on students and the socio-emotional learning during the conflict resolution process.